Effect of Repeated Annealing on Structural and Electrical Properties of Compound TI2-XHgXSr2-yBayCa2Cu3O10+δ (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
This Study includes preparation the Samples of the compound (Tl2-xHgxSr2-yBayCa2Cu3O10+8) by Using the solid-state reaction method using annealing method under different temperatures with hydrostatic pressures.  Found had been that the best annealing temperature is 850OC and best hydrostatic pressure is 8ton/cm2 .X-ray diffraction for the prepared compound showed that it has a crystalline structure Tetragonal type. At the molecular compensation for the, compound with different rates of (x,y) equal  (x= 0.3, y=0.1, 0.2). The compound keeps on its Tetragonal type at the molecular compensation where the critical temperature increased from 142⁰K to 144⁰K at the compensation rate of (x=0.3, y=0.1). But when the compensation rate of (x) and (y) increased a change occurred in the crystalline structure. showed that it has a crystalline structure of Tetragonal type. When repeated annealing the critical temperature for the compound increased from 144⁰K to 147⁰K at the rate (x=0.3, y=0.2).  Increased, a change occurred in the crystalline structure Also, in this research, study the samples; examine the crystalline, surface, qualitative and quantitative structure by the scanning electron microscope; finding the rates of the elements in the compound, and the impact of the molecular compensation in the elements for the compound; determine the percentage of oxygen and quantitative composition of the elements in the compound.